2010
DOI: 10.1016/j.virol.2010.07.039
|View full text |Cite
|
Sign up to set email alerts
|

An important role of the heat shock response in infected cells for replication of baculoviruses

Abstract: Baculoviruses serve as a stress factor that can activate both death-inducing and cytoprotective pathways in infected cells. In this report, induction of heat shock proteins (HSPs) of the 70-kDa family (HSP/HSC70) in Sf-9 cells after infection with AcMNPV was monitored by Western blot analysis. Two-dimensional electrophoresis in polyacrylamide gel revealed changes in the cellular pattern of HSP/HSC70s and synthesis of a new member of the HSP/HSC70 family in the infected cells. Although infection with AcMNPV mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 30 publications
3
36
0
Order By: Relevance
“…The induction of heat shock proteins (HSPs) of the 70-kDa family (HSP/HSC70) in Sf-9 cells after infection with AcMNPV was monitored by Western blot analysis (Lyupina et al,2010). were selected through stringent procedure after considering their economic value to the sericulture industry.…”
Section: Discussionmentioning
confidence: 99%
“…The induction of heat shock proteins (HSPs) of the 70-kDa family (HSP/HSC70) in Sf-9 cells after infection with AcMNPV was monitored by Western blot analysis (Lyupina et al,2010). were selected through stringent procedure after considering their economic value to the sericulture industry.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our findings regarding the IE2 and HSP relationship in a mammalian system, we hypothesized that HSPs stimulate IE2 protein stabilization. To verify this hypothesis, we examined IE2 protein levels upon treatment with a heat shock response inhibitor, KNK437, which has also previously been applied in an insect cell system [23]. As shown in Fig 9A, upon baculovirus infection of Sf cells, IE2 protein was detectable as early as 2 hpi, followed by a decrease after 4 and hsc70 (A2) genes were quantified by RT-qPCR using specific primers.…”
Section: Hsps Stabilize the Ie2 Protein During Baculovirus Infectionmentioning
confidence: 94%
“…Although a previous study has shown that inhibition of the heat shock response decreased the levels of viral replication in infected cells [23], the viral factor(s) that are responsible for this show that at 48 hpt, IE2 formed mature nuclear bodies that included a high concentration of G-actin (green) and enlarged, activated Pol II dots (red). KNK437 treatment alone (panels e to h) led to a failure in IE2 nuclear body formation as well as G-actin and activated Pol II recruitment, whereas for KNK437 in combination with MG132 (panels i to l), mature IE2 nuclear bodies could again be observed.…”
Section: The Interplay Between Hsc70 and Ie2 During Baculovirus Infecmentioning
confidence: 94%
See 2 more Smart Citations